The half moon : a novel - Keane, Mary Beth (Scribner, 2023)
"From the beloved bestselling author of Ask Again, Yes, an unforgettable novel about a couple in a small town and the complexities of marriage, family, longing, and desire. Malcolm Gephardt, handsome and gregarious longtime bartender at the Half Moon, has always dreamed of owning a bar. When his boss finally retires, Malcolm stretches to buy the place. He sees unquantifiable magic and potential in the Half Moon and hopes to transform it into a bigger success, but quickly realizes that making margins won't be easy. His smart and confident wife, Jess, has devoted herself to her law career. After years of trying to have a baby, she is struggling to accept the idea that motherhood may not be in the cards for her. Like Malcolm, she feels her youth beginning to slip away and wonders how to reshape her future. Award-winning author Mary Beth Keane's new novel takes place over the course of a week when Malcolm learns shocking news about Jess, a patron of the bar goes missing, and a blizzard hits the town, trapping everyone in place. With a deft eye and generous spirit, Keane explores the disappointments and unexpected consolations of midlife, the many forms forgiveness can take, and what it means to be a family"--